A photocurable slurry, organic hydrogel and preparation method thereof for highly elastic wearable strain sensor

By using photocuring slurry containing monomers, water retention agents, chemical crosslinkers, photoinitiators and ion-conducting fillers, organic hydrogel strain sensors are prepared, which solves the problems of easy dehydration and poor resilience of traditional sensors, and realizes the High elastic and good resilience sensors support large-scale production and customized applications.

CN116284566BActive Publication Date: 2025-02-14SOUTHERN UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211102263.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-09
Publication Date
2025-02-14
Estimated Expiration
2042-09-09

AI Technical Summary

Technical Problem

Traditional organic hydrogel strain sensors are prone to dehydration and have poor resilience, resulting in inaccurate electrical signal feedback and short service life, and complex preparation process, which limits large-scale production and customized applications.

Method used

Using a photocuring slurry including monomers, water retention agents, chemical crosslinking agents, photoinitiators and ion-conducting fillers, organic hydrogels are prepared by photocuring technology, combined with polyethylene glycol diacrylate as chemical crosslinking to increase covalent crosslinking points and improve rebound performance.

Benefits of technology

It realizes high elasticity and good resilience of organic hydrogels, improves the stability and service life of the sensor, simplifies the preparation process, and supports large-scale production and customized applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116284566B_ABST
    Figure CN116284566B_ABST
Patent Text Reader

Abstract

The present invention discloses a photocurable slurry, an organic hydrogel and a preparation method and application thereof which can be used for a highly elastic wearable strain sensor, and belongs to the technical field of flexible wearable electronic device materials; the present invention discloses a photocurable slurry, an organic hydrogel and a preparation method thereof which can be used for a highly elastic wearable strain sensor, and controls the components in the photocurable slurry by reasonable arrangement and the preparation method of the organic hydrogel; significantly improves the resilience performance of the organic hydrogel sensor; the cured organic hydrogel has good water absorption / water retention, is stretchable, has good resilience, and is used as a wearable strain sensor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of flexible wearable electronic device materials, and more specifically, relates to a photocurable slurry, an organic hydrogel and a preparation method thereof that can be used for a highly elastic wearable strain sensor. Background Art

[0002] Organic hydrogel strain sensors have good flexibility and can be attached to the surface of human skin. They have important applications in health monitoring, artificial intelligence, electronic skin and other fields. Their working principle is to convert external mechanical signals into easy-to-process electrical signals.

[0003] However, traditional organic hydrogel strain sensors have the following disadvantages: 1. Organic hydrogels are easy to dehydrate, which affects the stability of the sensor; 2. Organic hydrogels cannot rebound completely, so that there is obvious hysteresis during use and the mechanical strength decreases seriously, resulting in inaccurate electrical signal feedback and greatly reduced service life. In addition to the problems with organic hydrogel performance, the preparation of organic hydrogel strain sensors is still challenging. Traditional preparation technology has a long preparation time and complex procedures, which greatly limits the large-scale production of strain sensors. In addition, traditional methods can only prepare simple structures, such as squares and long strips, which limits the customization and wearable applications of strain sensors. With the development of intelligence and customization of wearable electronic products, it is crucial to develop organic hydrogel strain sensors with diverse structures.

[0004] 3D printing is different from traditional preparation processes. It forms objects by stacking layers. As one of the most mature 3D printing technologies, photocuring 3D printing is widely used to prepare high-precision structures. Its curing principle is to irradiate photosensitive resin with ultraviolet light to cause free radical polymerization. Although commercial elastic photosensitive resin has good elasticity, its stretchability is poor and cannot meet the needs of strain sensors. Therefore, it is urgent to develop photocurable slurries for stretchable, highly elastic and wearable strain sensors. Summary of the invention

[0005] 1. Problem to be solved

[0006] In view of the problem of poor performance of flexible wearable electronic device materials in the prior art, a photocurable slurry, an organic hydrogel and a preparation method thereof that can be used for a highly elastic wearable strain sensor are provided. The above technical problems are improved by the reasonable setting of the components in the photocurable slurry and the control of the preparation method of the organic hydrogel.

[0007] 2. Technical solution

[0008] In order to solve the above problems, the technical solution adopted by the present invention is as follows:

[0009] The present invention discloses an organic hydrogel that can be used for a highly elastic wearable strain sensor, comprising a monomer, a water retaining agent, a chemical crosslinking agent, a photoinitiator and an ion-conducting filler, wherein the monomer is acryloylmorpholine, and the chemical crosslinking agent is polyethylene glycol diacrylate.

[0010] Preferably, the contents of the monomer, water retaining agent, chemical crosslinking agent, photoinitiator and ion-conducting filler are respectively:

[0011]

[0012] Preferably, the water retaining agent is one or more of glycerol, ethylene glycol and propylene glycol.

[0013] Preferably, the photoinitiator is phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide.

[0014] Preferably, the ion-conducting filler is sodium chloride.

[0015] Preferably, the organic hydrogel is prepared from a photocurable slurry that can be used for a highly elastic wearable strain sensor, and the photocurable slurry that can be used for a highly elastic wearable strain sensor is the above-mentioned photocurable slurry.

[0016] The present invention provides a method for preparing an organic hydrogel that can be used for a highly elastic wearable strain sensor. The organic hydrogel that can be used for a highly elastic wearable strain sensor is the above-mentioned organic hydrogel, and the preparation method thereof is as follows:

[0017] S1, mixing monomers, photoinitiators, ion-conducting fillers and grinding aids, and then performing the first stage of ball milling to obtain monomer slurry; after the first stage of ball milling, adding a water-retaining agent and a chemical cross-linking agent to the monomer slurry, and then performing the second stage of ball milling, and filtering the grinding aids in the second stage of ball milling to prepare a light-cured slurry;

[0018] S2, subjecting the photocurable slurry to ultraviolet light curing and molding;

[0019] S3. After UV curing and molding, water absorption is performed to prepare an organic hydrogel that can be used for a highly elastic wearable strain sensor.

[0020] Preferably, after preparing the photocurable slurry in S1, the photocurable slurry is placed in a dry environment to prevent the photocurable slurry from absorbing water.

[0021] Preferably, the wavelength of ultraviolet light in S2 is 405nm, the layer thickness is 2-100μm, and the intensity of ultraviolet light is 2-30mW / cm 2 , exposure time is 0.1-20s.

[0022] Preferably, the water absorption environment in S3 is: temperature: 22-27° C., humidity: 40-65%, and water absorption for 12-720 hours.

[0023] A strain sensor of the present invention is prepared from the organic hydrogel of claim 5.

[0024] The present invention discloses an application of an organic hydrogel that can be used for a highly elastic wearable strain sensor, and uses the organic hydrogel as a material for the strain sensor.

[0025] 3. Beneficial effects

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] (1) An organic hydrogel that can be used for a highly elastic wearable strain sensor of the present invention comprises a monomer, a water retaining agent, a chemical crosslinking agent, a photoinitiator and an ion-conducting filler, wherein the monomer is acryloylmorpholine, and the chemical crosslinking agent is polyethylene glycol diacrylate; the water retaining agent is introduced into the acryloylmorpholine organic hydrogel to effectively reduce its saturated vapor pressure, thereby ensuring the water retention performance of the subsequent organic hydrogel product; in addition, the introduction of polyethylene glycol diacrylate can increase the covalent crosslinking points of the polymer in the acryloylmorpholine / water retaining agent, thereby significantly improving the resilience performance of the organic hydrogel sensor; the cured organic hydrogel has good water absorption / water retention, is stretchable, and has good resilience, and is used as a wearable strain sensor.

[0028] (2) A method for preparing an organic hydrogel that can be used for a highly elastic wearable strain sensor of the present invention, wherein the organic hydrogel that can be used for a highly elastic wearable strain sensor is the organic hydrogel described above, and the preparation method thereof is as follows: S1, mixing a monomer, a photoinitiator, an ion-conducting filler and a grinding aid, and after mixing, performing a first stage of ball milling to obtain a monomer slurry; after the first stage of ball milling, adding a water-retaining agent and a chemical cross-linking agent to the monomer slurry, and then performing a second stage of ball milling, and filtering the grinding aid during the second stage of ball milling to obtain a photocurable slurry; S2, performing ultraviolet light curing molding on the photocurable slurry; S3, ultraviolet light After curing and molding, water is absorbed to prepare an organic hydrogel that can be used for highly elastic wearable strain sensors. In the above steps, the monomer, water-retaining agent, chemical cross-linking agent, photoinitiator and ion-conducting filler are mixed and ball-milled in stages to achieve a photocuring system formed by the monomer, photoinitiator and ion-conducting filler. Then, through the second stage of ball milling, the water-retaining agent and chemical cross-linking agent are locally water-retaining and chemically cross-linked around the photocuring system, thereby improving the subsequent photocuring effect, and also helping the final product solve the technical problems of easy dehydration, poor resilience and customized wear of existing photocuring slurries and printed organic hydrogel products. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1The relative mass changes of the products cured by acryloyl morpholine, acryloyl morpholine / glycerol, and acryloyl morpholine / glycerol / polyethylene glycol diacrylate;

[0030] Figure 2 Middle: Tensile and rebound photos of (a) acryloylmorpholine / glycerol and (b) acryloylmorpholine / glycerol / polyethylene glycol diacrylate cured products;

[0031] Figure 3 Middle: Stress-strain curves of (a) acryloylmorpholine / glycerol and (b) acryloylmorpholine / glycerol / polyethylene glycol diacrylate cured products after 100 cycles at a tensile strain of 100%;

[0032] Figure 4 The relative resistance change of acryloylmorpholine / glycerol / polyethylene glycol diacrylate cured product under different strains;

[0033] Figure 5 This is a photo of a 3D printed acryloylmorpholine / glycerol / polyethylene glycol diacrylate cured product with a porous structure and its usage status. DETAILED DESCRIPTION

[0034] The following more detailed description of the embodiments of the present invention is not intended to limit the scope of the claimed invention, but is merely for illustration and not to limit the description of the features and characteristics of the present invention, in order to propose the best mode for carrying out the present invention, and to be sufficient to enable those skilled in the art to implement the present invention. However, it should be understood that various modifications and variations may be made without departing from the scope of the present invention as defined by the appended claims. The detailed description and the accompanying drawings should be considered only as illustrative, not restrictive, and if there are any such modifications and variations, they will all fall within the scope of the present invention described herein. In addition, the background technology is intended to illustrate the current status and significance of the research and development of the present technology, and is not intended to limit the present invention or the application field of the present application and the present invention.

[0035] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which the present invention belongs; the terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention; the term "and / or" used herein includes any and all combinations of one or more related listed items.

[0036] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.

[0037] The present invention is further described below in conjunction with specific embodiments.

[0038] Example 1

[0039] 1) Preparation of acryloylmorpholine / glycerol / polyethylene glycol diacrylate photocurable slurry

[0040] Weigh 69.3g of acryloylmorpholine, 0.7g of TPO, 0.05g of sodium chloride, and 300g of zirconium oxide balls, add them to a 250ml zirconium oxide ball mill, and mill them at a speed of 360r / min for 10min to obtain acryloylmorpholine slurry. Add 30g of glycerol and 0.25g of polyethylene glycol diacrylate to the ball mill, mill them at a speed of 360r / min for 30min, filter out the zirconium oxide balls with a colander to obtain acryloylmorpholine / glycerol / polyethylene glycol diacrylate photocurable slurry and store it in a sealed container to prevent the photosensitive resin from absorbing water and affecting photocurable printing. After the resin absorbs water, it will increase the adhesion of the printed product, making it difficult to remove the printed sample from the platform.

[0041] 2) Preparation of acryloylmorpholine / glycerol / polyethylene glycol diacrylate photocurable 3D printed products

[0042] The slurry prepared above was cured by UV light using a photocuring 3D printer. The UV light wavelength was 405 nm, the layer thickness was 20 μm, and the UV light intensity was 5 mW / cm 2 , the exposure time is 3s. A printed product with acryloylmorpholine / glycerol / polyethylene glycol diacrylate was prepared. The product was placed at room temperature (temperature: 22-27°C, humidity: 40-65%) to absorb water for 24 hours to obtain an acryloylmorpholine / glycerol / polyethylene glycol diacrylate organic hydrogel.

[0043] Example 2

[0044] 1) Preparation of acryloylmorpholine / glycerol / polyethylene glycol diacrylate photocurable slurry

[0045] Weigh 69.3g of acryloylmorpholine, 0.7g of TPO, 0.05g of sodium chloride, and 300g of zirconium oxide balls, add them to a 250ml zirconium oxide ball mill, and mill them at a speed of 360r / min for 10min to obtain acryloylmorpholine slurry. Add 30g of glycerol and 0.5g of polyethylene glycol diacrylate to the ball mill, mill them at a speed of 360r / min for 30min, filter out the zirconium oxide balls with a colander to obtain acryloylmorpholine / glycerol / polyethylene glycol diacrylate photocurable slurry and store it in a sealed container to prevent the photosensitive resin from absorbing water and affecting photocurable printing. After the resin absorbs water, it will increase the adhesion of the printed product, making it difficult to remove the printed sample from the platform.

[0046] 2) Preparation of acryloylmorpholine / glycerol / polyethylene glycol diacrylate photocurable 3D printed products

[0047] The slurry prepared above was cured by UV light using a photocuring 3D printer. The UV light wavelength was 405 nm, the layer thickness was 20 μm, and the UV light intensity was 5 mW / cm 2 , the exposure time is 3s. A printed product with acryloylmorpholine / glycerol / polyethylene glycol diacrylate was prepared. The product was placed at room temperature (temperature: 22-27°C, humidity: 40-65%) to absorb water for 24 hours to obtain an acryloylmorpholine / glycerol / polyethylene glycol diacrylate organic hydrogel.

[0048] Example 3

[0049] 1) Preparation of acryloylmorpholine / glycerol / polyethylene glycol diacrylate photocurable slurry

[0050] Weigh 69.3g of acryloylmorpholine, 0.7g of TPO, 0.05g of sodium chloride, and 300g of zirconium oxide balls, add them to a 250ml zirconium oxide ball mill, and mill them at a speed of 360r / min for 10min to obtain acryloylmorpholine slurry. Add 30g of glycerol and 1g of polyethylene glycol diacrylate to the ball mill, mill them at a speed of 360r / min for 30min, filter out the zirconium oxide balls with a colander to obtain acryloylmorpholine / glycerol / polyethylene glycol diacrylate photocurable slurry and store it in a sealed container to prevent the photosensitive resin from absorbing water and affecting photocurable printing. After the resin absorbs water, it will increase the adhesion of the printed product, making it difficult to remove the printed sample from the platform.

[0051] 2) Preparation of acryloylmorpholine / glycerol / polyethylene glycol diacrylate photocurable 3D printed products

[0052] The slurry prepared above was cured by UV light using a photocuring 3D printer. The UV light wavelength was 405 nm, the layer thickness was 20 μm, and the UV light intensity was 5 mW / cm 2 , the exposure time is 3s. A printed product with acryloylmorpholine / glycerol / polyethylene glycol diacrylate was prepared. The product was placed at room temperature (temperature: 22-27°C, humidity: 40-65%) to absorb water for 24 hours to obtain an acryloylmorpholine / glycerol / polyethylene glycol diacrylate organic hydrogel.

[0053] Example 4

[0054] 1) Preparation of acryloylmorpholine / glycerol / polyethylene glycol diacrylate photocurable slurry

[0055] Weigh 69.3g of acryloylmorpholine, 0.7g of TPO, 0.05g of sodium chloride, and 300g of zirconium oxide balls, add them to a 250ml zirconium oxide ball mill, and mill them at a speed of 360r / min for 10min to obtain acryloylmorpholine slurry. Add 30g of glycerol and 5g of polyethylene glycol diacrylate to the ball mill, mill them at a speed of 360r / min for 30min, filter out the zirconium oxide balls with a colander to obtain acryloylmorpholine / glycerol / polyethylene glycol diacrylate photocurable slurry and store it in a sealed container to prevent the photosensitive resin from absorbing water and affecting photocurable printing. After the resin absorbs water, it will increase the adhesion of the printed product, making it difficult to remove the printed sample from the platform.

[0056] 2) Preparation of acryloylmorpholine / glycerol / polyethylene glycol diacrylate photocurable 3D printed products

[0057] The slurry prepared above was cured by UV light using a photocuring 3D printer. The UV light wavelength was 405 nm, the layer thickness was 20 μm, and the UV light intensity was 5 mW / cm 2 , the exposure time is 3s. A printed product with acryloylmorpholine / glycerol / polyethylene glycol diacrylate was prepared. The product was placed at room temperature (temperature: 22-27°C, humidity: 40-65%) to absorb water for 24 hours to obtain an acryloylmorpholine / glycerol / polyethylene glycol diacrylate organic hydrogel.

[0058] Comparative Example 1

[0059] (1) Preparation of acryloylmorpholine photocurable slurry

[0060] Weigh 69.3 g of acryloyl morpholine, 0.7 g of TPO, 0.05 g of sodium chloride, and 300 g of zirconia balls, add them into a 250 ml zirconia ball mill, and ball mill at a speed of 360 r / min for 10 min. Filter out the zirconia balls with a colander to obtain acryloyl morpholine photocuring slurry.

[0061] (2) Preparation of acryloylmorpholine photocurable 3D printed products

[0062] The slurry prepared above was cured by UV light using a photocuring 3D printer. The UV light wavelength was 405 nm, the layer thickness was 20 μm, and the UV light intensity was 5 mW / cm 2 , the exposure time is 3s. A printed product with acryloyl morpholine is prepared. The product is placed at room temperature (temperature: 22-27°C, humidity: 40-65%) to absorb water for 24 hours to obtain an acryloyl morpholine organic hydrogel.

[0063] Comparative Example 2

[0064] 1) Preparation of acryloylmorpholine / glycerol photocurable slurry

[0065] Weigh 69.3g of acryloylmorpholine, 0.7g of TPO, 0.05g of sodium chloride, and 300g of zirconium oxide balls, add them to a 250ml zirconium oxide ball mill, and mill them at a speed of 360r / min for 10min to obtain acryloylmorpholine slurry. Add 30g of glycerol to the ball mill, mill them at a speed of 360r / min for 30min, filter out the zirconium oxide balls with a colander to obtain acryloylmorpholine / glycerol photocurable slurry and store it in a sealed container to prevent the photosensitive resin from absorbing water and affecting photocurable printing. After the resin absorbs water, it will increase the adhesion of the printed product, making it difficult to remove the printed sample from the platform.

[0066] 2) Preparation of acryloylmorpholine / glycerol photocurable 3D printed products

[0067] The slurry prepared above was cured by UV light using a photocuring 3D printer. The UV light wavelength was 405 nm, the layer thickness was 20 μm, and the UV light intensity was 5 mW / cm 2 , the exposure time is 3s. A printed product with acryloylmorpholine / glycerol was prepared. The product was placed under room temperature (temperature: 22-27°C, humidity: 40-65%) to absorb water for 24 hours to obtain an acryloylmorpholine / glycerol organic hydrogel.

[0068] The performance indicators of the photocurable slurries prepared in Examples 1 to 4 and Comparative Examples 1 to 2 were verified, as shown in Table 1. As can be seen from Table 1, in several embodiments, the resin viscosity is less than 60 mPa·s, which is suitable for photocurable 3D printing.

[0069] Table 1 Acryloylmorpholine / glycerol / polyethylene glycol diacrylate photocurable slurry

[0070]

[0071]

[0072] like Figure 1 As shown, pure acryloylmorpholine cured products, when placed at room temperature, first absorb water and then lose water, and have poor water retention performance; after adding glycerol, acryloylmorpholine / glycerol and acryloylmorpholine / glycerol / polyethylene glycol diacrylate cured products do not show obvious water loss, indicating that they have good water absorption / retention properties.

[0073] For acryloylmorpholine / glycerol cured products, due to the lack of sufficient chemical cross-linking points, acryloylmorpholine / glycerol cured products cannot fully recover after stretching (e.g. Figure 2a); The introduction of polyethylene glycol diacrylate increases the chemical cross-linking (covalent cross-linking points) of acryloyl morpholine. Sufficient covalent cross-linking points ensure that the cross-linking network of acryloyl morpholine / glycerol / polyethylene glycol diacrylate cured products is not destroyed when stretched, so acryloyl morpholine / glycerol / polyethylene glycol diacrylate cured products can fully rebound (such as Figure 2 b). Therefore, for the cyclic loading-unloading force test of the acryloylmorpholine / glycerol cured product, the residual strain of the acryloylmorpholine / glycerol cured product gradually increased, and the maximum stress decreased significantly, indicating that it has poor resilience (such as Figure 3 a); For the acryloylmorpholine / glycerol / polyethylene glycol diacrylate cured product, after two cycles of cyclic loading-unloading force test, the subsequent stress-strain curve area remained basically unchanged, indicating that the acryloylmorpholine / glycerol / polyethylene glycol diacrylate cured product has excellent resilience and fatigue resistance (such as Figure 3 b).

[0074] Since the cured product of acryloylmorpholine / glycerol / polyethylene glycol diacrylate has excellent resilience, the cured product can be used as a strain sensor. Under different strains, the resistance of the cured product of acryloylmorpholine / glycerol / polyethylene glycol diacrylate changes regularly and responds repeatedly, indicating that it has potential sensing performance (such as Figure 4 ).

[0075] Finally, the 3D printed acryloylmorpholine / glycerol / polyethylene glycol diacrylate cured product has structural design, and a ring with a hole structure can be prepared and worn directly on the finger. The bending movement of the finger causes the resistance of the acryloylmorpholine / glycerol / polyethylene glycol diacrylate cured product to change regularly and respond repeatedly, indicating that the 3D printed acryloylmorpholine / glycerol / polyethylene glycol diacrylate cured product can be used as a potential wearable organic hydrogel strain sensor (such as Figure 5 ).

[0076] The present invention has been described in detail above in conjunction with specific exemplary embodiments. However, it should be understood that various modifications and variations may be made without departing from the scope of the present invention as defined by the appended claims. The detailed description and the accompanying drawings should be considered only as illustrative and not restrictive, and if there are any such modifications and variations, they will fall within the scope of the present invention described herein. In addition, the background technology is intended to illustrate the current status and significance of the research and development of the present technology and is not intended to limit the present invention or the application field of the present application and the present invention.

[0077] More specifically, although exemplary embodiments of the present invention have been described herein, the present invention is not limited to these embodiments, but includes any and all embodiments that are recognizable by those skilled in the art based on the foregoing detailed description, such as combinations between the various embodiments, adaptive changes and / or replacements. The limitations in the claims may be interpreted broadly based on the language used in the claims and are not limited to the examples described in the foregoing detailed description or during the implementation of the application, which examples should be considered non-exclusive. Any steps listed in any method or process claim may be performed in any order and are not limited to the order presented in the claim. Therefore, the scope of the present invention should be determined solely by the attached claims and their legal equivalents, rather than by the description and examples given above.

[0078] Unless otherwise limited, all technology and scientific terms used herein have the same meaning as those of ordinary skill in the art to which the present invention belongs. When there is a contradiction, the definition in this specification sheet shall prevail. When molar weight, quality, concentration, temperature, time, volume or other value or parameter are represented by a range, a preferred range, or a series of upper preferred values ​​and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any upper range limit or preferred value and any lower range limit or preferred value, regardless of whether the scope is disclosed separately. For example, a range of 1-50 is understood to include any number, combination of numbers, or subrange selected from 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, or 50, and all decimal values ​​between the above integers, for example, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, and 1.9. With respect to subranges, "nested subranges" extending from any endpoint within the range are specifically contemplated. For example, nested sub-ranges of the exemplary range 1-50 may include 1-10, 1-20, 1-30, and 1-40 in one direction, or 50-40, 50-30, 50-20, and 50-10 in the other direction.

Claims

1. A photocurable slurry for a highly elastic wearable strain sensor, characterized in that: The invention is composed of a monomer, a water retaining agent, a chemical crosslinking agent, a photoinitiator and an ion-conducting filler, wherein the monomer is acryloylmorpholine, the water retaining agent is one or more of glycerol, ethylene glycol and propylene glycol, the chemical crosslinking agent is polyethylene glycol diacrylate, and the photoinitiator is phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide; The percentages of the monomer, water retaining agent, chemical crosslinking agent, photoinitiator and ion-conducting filler are respectively:

2. The photocurable slurry for a highly elastic wearable strain sensor according to claim 1, characterized in that: The ion-conducting filler is sodium chloride.

3. An organic hydrogel that can be used for a highly elastic wearable strain sensor, characterized in that: The organic hydrogel is prepared from a photocurable slurry that can be used for a highly elastic wearable strain sensor, and the photocurable slurry that can be used for a highly elastic wearable strain sensor is the photocurable slurry according to any one of claims 1 to 2.

4. A method for preparing an organic hydrogel that can be used for a highly elastic wearable strain sensor, characterized in that: The organic hydrogel that can be used for a highly elastic wearable strain sensor is the organic hydrogel according to claim 3, and the preparation method thereof is as follows: S1, mixing monomers, photoinitiators, ion-conducting fillers and grinding aids, and then performing the first stage of ball milling to obtain monomer slurry; after the first stage of ball milling, adding a water-retaining agent and a chemical cross-linking agent to the monomer slurry, and then performing the second stage of ball milling, and filtering the grinding aids in the second stage of ball milling to prepare a light-cured slurry; S2, subjecting the photocurable slurry to ultraviolet light curing and molding; S3. After UV curing and molding, water absorption is performed to prepare an organic hydrogel that can be used for a highly elastic wearable strain sensor.

5. The method for preparing an organic hydrogel that can be used for a highly elastic wearable strain sensor according to claim 4, characterized in that: After preparing the photocurable slurry, place it in a dry environment to prevent the photocurable slurry from absorbing water.

6. The method for preparing an organic hydrogel for a highly elastic wearable strain sensor according to claim 4, characterized in that: The wavelength of UV light in S2 is 405nm, the layer thickness is 2-100μm, and the UV intensity is 2-30mW / cm 2 , the exposure time is 0.1-20s; and / or, the water absorption environment in S3 is: temperature: 22-27°C, humidity: 40-65%, and water absorption for 12-720h.

7. A strain sensor, characterized in that: Prepared from the organohydrogel according to claim 3.

8. An application of an organic hydrogel for a highly elastic wearable strain sensor, characterized in that: It is used as the material of strain sensor.

Citation Information

Patent Citations

  • High-tensile conductive hydrogel for photo-curing 3D printing and preparation method thereof

    CN111423536A

  • Photocurable 3D printing conductive ionic gel, special photosensitive resin and preparation method of photosensitive resin

    CN113717324A